2013
DOI: 10.1523/jneurosci.1611-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Cortical Dysfunction in a Mouse Model of a Schizophrenia-Related Microdeletion

Abstract: We used a mouse model of the schizophrenia-predisposing 22q11.2 microdeletion to evaluate how this genetic lesion affects cortical neural circuits at the synaptic, cellular, and molecular levels. Guided by cognitive deficits, we demonstrated that mutant mice display robust deficits in high-frequency synaptic transmission and short-term plasticity (synaptic depression and potentiation), as well as alterations in long-term plasticity and dendritic spine stability. Apart from previously reported reduction in dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
87
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 78 publications
14
87
2
Order By: Relevance
“…We have previously shown that Df(16)A +/− mice exhibit a robust PPI deficit (12). Analysis by genotype [repeated measures (RM) ANOVA, prepulse × genotype interaction F(12, 224) = 1.981, P = 0.027; main effect of genotype F(3, 56) = 8.308, P < 0.001] confirmed our previous result [Df (16)A +/− vs. WT, Bonferroni post hoc analysis, P < 0.0001; Fig. 1A Fig.…”
Section: Restoration Of Mirta22 Levels Prevents Deficits In Ppi Wm-dsupporting
confidence: 85%
See 2 more Smart Citations
“…We have previously shown that Df(16)A +/− mice exhibit a robust PPI deficit (12). Analysis by genotype [repeated measures (RM) ANOVA, prepulse × genotype interaction F(12, 224) = 1.981, P = 0.027; main effect of genotype F(3, 56) = 8.308, P < 0.001] confirmed our previous result [Df (16)A +/− vs. WT, Bonferroni post hoc analysis, P < 0.0001; Fig. 1A Fig.…”
Section: Restoration Of Mirta22 Levels Prevents Deficits In Ppi Wm-dsupporting
confidence: 85%
“…Specifically, the mice exhibit hyperactivity, decrease in prepulse inhibition (PPI) that is indicative of sensorimotor gating deficits, working memory (WM) abnormalities, social memory (SM) deficits, and associative (fear) memory deficits (12). In addition to the observed behavioral abnormalities, Df(16)A +/− mice also show alterations in the dendritic development of cortical neurons, as well as deficits in several forms of prefrontal cortical synaptic plasticity, which also emerge in part due to miRNA dysregulation (16). If the sustained postnatal elevation of Mirta22 levels hinders normal development of circuits and behaviors, one prediction would be that LoF mutations of Mirta22 will have beneficial effects, preventing the emergence of at least some of these deficits.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…ELS also have been shown to increase short-term plasticity in the mesial prefrontal cortex (mPFC) (Hernan et al 2013). Alterations in short-term plasticity in the mPFC have been associated with changes in hippocampal-PFC synchrony (Sigurdsson et al 2010;Fenelon et al 2013). Taken together, these findings suggest there is a long-standing increase in the E/I ratio in the mPFC.…”
Section: Altered E/i Balance and Connectivitymentioning
confidence: 91%
“…Increases in spine formation and elimination have been found in animal models for Fragile X syndrome, 50,51 Rett syndrome 52 and schizophrenia. 53 In neurodegenerative disease models, similar increases of spine turnover are observed and it will follow by subsequent net loss of spines, for example, in Alzheimer disease, 54,55 prion disease 56 and Huntington disease. 57 In the stroke model, severe ischemia caused a rapid loss of spine and dendrite structure within 10 minutes.…”
Section: Structural Plasticity Of Dendritic Spinesmentioning
confidence: 94%